Comparison of the Effect of Contextual Schema Therapy and Emotion Efficacy Therapy on Interpersonal Sensitivity, Coping Self-efficacy and Focus of Attention in Adolescent Girls with Social Anxiety - Masumeh Hayati; Manijeh Shehni Yailagh; Moloud Keykhosrovani (Iranian Evolutionary Educational Psychology Journal)
Objective: The purpose of this study was to compare the effect of contextual schema therapy and emotion efficacy therapy on interpersonal sensitivity, coping self-efficacy and focus of attention in adolescent girls with social anxiety. Methods: The research method was a field experiment with a pre-test-post-test design with a control group and a one-month follow-up. The statistical population included all female students of the second secondary level between 15 and 16 years of age in Barazjan who were studying in 1400-1401 school year. At first, the Social Phobia Inventory was completed by the students and 60 students whose social anxiety score was one standard deviation above the mean were randomly selected and assigned to two experimental groups and one control group (20 people in each group). Before the implementation of the intervention, the scales of interpersonal sensitivity, coping self-efficacy, and focus of attention were completed by samples. After that, in experimental group 1, contextual schema therapy based on the protocol of Roediger et al. (2018) and in experimental group 2 emotion efficacy therapy using McKay and West (2016) protocol, during 8 sessions of 70 minutes were implemented for two months (one session every week) and the control group did not receive any intervention. To analyze the data, multivariate covariance analysis was used using SPSS-25 software. Results: The results showed both contextual schema therapy and emotional efficiency-based therapy have an effect on interpersonal sensitivity, coping self-efficacy and the focus of attention of female students with social anxiety and this effect is lasting over time (p<0.001). Conclusions: According to these results, it is suggested that the Ministry of Education and its related institutions seek to plan for the education of children and teenagers using the approach of contextual schema therapy and also therapy based on emotional efficiency.